EDUKASI LITERASI KEUANGAN MENUJU UMKM SUKSES DI DESA GEMBONGAN KECAMATAN SIGALUH KABUPATEN BANJARNEGARA - Ainiyah, Ghonimah Zumroatun; Maharani, Destin Alfianika (STIE Pelita Nusantara, 2025)
The purpose of this training activity is to provide understanding to MSME actors in partner villages about income, costs, and profits. The location of this event is Gembongan Village in Sigaluh District, Banjarnegara Regency. Gembongan Village has a community that mostly consists of micro, small and medium enterprises (MSMEs). Among them are MSMEs that sell honey bananas, dried combro, herbal medicine, various dry snacks, and gutela, which is sugar made from cassava. Because it is considered the right step to encourage people's business tastes and increase financial literacy for business owners, this activity is intended for business owners. They must also know about all costs and profits. This activity helps MSME actors understand financial management and the right financial management system.